Determination of Verapamil in Exhaled Breath Condensate by Using Microextraction and Liquid Chromatography - Pourkarim, Fariba; Shayanfar, Ali; Khoubnasabjafari, Maryam; Akbarzadeh, Fariborz; Sajedi-Amin, Sanaz; Jouyban-Gharamaleki, Vahid; Jouyban, Abolghasem (Current Pharmaceutical Analysis, 2019)
Background: Developing a simple analysis method for quantification of drug concentration is one of the essential issues in pharmacokinetic and therapeutic drug monitoring studies. Objective: A fast and reliable dispersive liquid-liquid microextraction procedure was employed for preconcentration of verapamil in exhaled breath condensate (EBC) samples and this was followed by the determination with high-performance liquid chromatography-ultraviolet detection. Methods: A reverse-phase high-performance liquid chromatography (RP-HPLC) combined with a dispersive liquid-liquid microextraction method (DLLME) was applied for quantification of verapamil in the EBC samples. The developed method was validated according to FDA guidelines. Results: Under the optimum conditions, the method provided a linear range between 0.07 and 0.8 μg.mL-1 with a coefficient of determination of 0.998. The intra- and inter-day relative standard deviation and relative error values of the method were below 15%, which indicated good precision and accuracy. The proposed method was successfully applied for the analysis of verapamil in two real samples with concentrations of 0.07 and 0.09 μg.mL-1. Conclusion: The established HPLC-UV-DLLME method could be applied for the analysis of verapamil in human EBC samples.
Keywords: mortality